SEJARAH JARINGAN HIDAYATULLAH DI MINAHASA : PESANTREN DAN POLITIK DAKWAH - Rusli, Almunauwar Bin (Center for Research and Development of Religious Literature and Heritage, Agency for Research and Development and Training, Ministry of Religious Affairs of the Republic of Indonesia, 2020)
This article will look at the polemics of identity between Muslim and Christian in Minahasa from educational culture perspective has received less serious attention. This article employs a qualitative descriptive method with sociological approach. Participatory observations, in-depth interviews and literature studies were conducted at Tomohon 2018. The result of research shows that Hidayatullah pesantren teach the doctrine of tauhid, sharia and muamalah in the passion way. While daâ€™wah politics are their strategy to spread the truth of Islam to Christian society with mubaligh diaspora, marriage of mubarakah and distribution of the Hidayatullah magazine. The presence of Hidayatullah in Minahasa supporting the spirit of santrinization. They want to facilitate santri to practice the Islamic values to the fullest as well as establishing the believe that Islam sits on the most honorable place in Indonesia. The santrinization created the loyalty and obedience to the leaders in order to defend Islam from the attacks of the infidels group. Keywords: Hidayatullah Networks, Pesantren, Daâ€™wah Politics, Minahasa Â Artikel ini ingin melihat polemik identitas antara Muslim dan Kristen di Minahasa dari perspektif budaya pendidikan yang kurang mendapat perhatian serius. Studi ini menggunakan metode kualitatif-deskriptif dengan pendekatan sosiologis. Observasi partisipatif, wawancara mendalam dan studi literatur dilakukan di Tomohon 2018. Hasil penelitian menunjukan bahwa pesantren mengajarkan doktrin tauhid, syariah dan muamalah dengan cara yang penuh gairah. Sedangkan politik dakwah menjadi strategi mereka dalam menyebarluaskan kebenaran Islam kepada masyarakat Kristen melalui diaspora mubaligh, pernikahan mubarakah dan distribusi majalah Hidayatullah. Kehadiran Hidayatullah di Minahasa mendukung semangat santrinisasi. Mereka ingin memfasilitasi santri dalam rangka menunaikan ajaran Islam secara kaffah seraya meneguhkan keyakinan bahwa Islam tetap menduduki tempat terhormat di Indonesia. Santrinisasi melahirkan kesetiaan dan kepatuhan kepada pemimpin dalam membela Islam dari serangan kaum kafir. Kata kunci: Jaringan Hidayatullah, Pesantren, Politik Dakwah, Minahasa